Compatibilidade de Agrotóxicos com os Ácaros Predadores Neoseiulus californicus (McGregor) e Phytoseiulus macropilis (Banks) (Acari: Phytoseiidae) - Poletti, Marcelo; Collette, Lúcio; Omoto, Celso (BioAssay, 2009)
One of the strategies to manage Tetranychus urticae Koch is the use of applied biological control by releasing phytoseiid mites (Acari: Phytoseiidae). However, the use of pesticides can affect the survivorship and reproduction of these biological control agents. The objective of this study was to evaluate the compatibility of 21 pesticides (acaricideinsecticides, insecticides and fungicides) on immature and adult stages of the predaceous mites Neoseiulus californicus (McGregor) and Phytoseiulus macropilis (Banks). Each pesticide was tested at concentrations that were recommended to control the pests in ornamental and vegetable crops in Brazil. The mortality of immature and adult of each predaceous mite was assessed 120 and 48 h after spraying the pesticide, respectively. The impact of pesticides on instantaneous growth rate (ri) was also assessed. Among the pesticides, two acaricide-insecticides (fenpropathrin and milbemectin), two insecticides (buprofezin and spinosad) and eight fungicides (azoxystrobin, metiram+pyraclostrobin, boscalid+kresoxim-methyl, tebuconazole, clorotalonil, imibenconazole, iprodione, triforine) had no effect on survivorship and reproduction of N. californicus. Six fungicides were compatible with P. macropilis (azoxystrobin, boscalid+kresoxim-methyl, tebuconazole, imibenconazole, iprodione e triforine). The highest toxicity to N. californicus was observed with pyridaben. Besides the high mortality of P. macropilis caused by fenpropathrin, beta-cypermethrin, formetanate, methomyl and pyridaben, these pesticides led to the extinction of mite population. Because of the tolerance of N. californicus to several pesticides, these predaceous mites have showed high potential to be used in commercial field crops.